Fatigue reliability analysis of tunnelling boring machine cutterhead with cracks. (November 2022) - Li, Jie; Zhang, Bin; Lyu, Dong; Guo, Jingbo; Su, Kang; Hu, Bo
Highlights: The fatigue crack propagation rate model of cutterhead under different reliability was established and the damage tolerance of cutterhead is Proposed. The dangerous position of cutterhead failure was determined by using finite element method. The fatigue propagation life of cutterhead under different reliability was calculated using the Paris model. The main factors affecting the reliability of cutterhead were analyzed. Abstract: The cutterhead of the tunnel boring machine (TBM) is a large-scale metal welded structure, which is prone to some problems such as wear and cracking during the tunnelling process. Considering this phenomenon, a damage tolerance based fatigue crack propagation rate model for the cutterhead with different reliability is established in this paper. Based on the fatigue load spectrum, the fatigue propagation life of the cutterhead with different reliability is calculated, the main factors affecting the reliability of the cutterhead are analyzed, and the engineering experiment is carried out. The results of finite element analysis show that three dangerous failure positions of the cutterhead are the junction of the split plane, the maximum deformation of the block and the center cutter seat. The load stress amplitude and initial crack size are the main factors affecting the crack propagation life and the reliability of the cutterhead. As the load stress amplitude and the initial crack size of the cutterhead increase, the fatigue crack propagation life and the reliability of the cutterhead decrease. Moreover, when the initial crack size of the cutterhead is greater than 0.5 mm, the fatigue crack propagation life of the cutterhead decreases dramatically. The research results provide a scientific basis for the crack detection, the life prediction and the reliability evaluation of the cutterhead.